2013
DOI: 10.5121/ijaia.2013.4109
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining and Neural Network Techniques in Stock Market Prediction : A Methodological Review

Abstract: Prediction in any field is a complicated, challenging and daunting process. Employing traditional methods may not ensure the reliability of the prediction. In this paper, we are reviewing the possibility of applying two well-known techniques neural network and data mining in stock market prediction. As neural network is able to extract useful information from a huge data set and data mining is also able to predict future trends and behaviors. Therefore, a combination of both these techniques could make the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The research in data mining and neural networks techniques [7] has employed traditional methods that may not ensure the reliability of the prediction. In this paper, They basically go over the two techniques namely mining of data and the neural network in artificial intelligence.…”
Section: Literature Surveymentioning
confidence: 99%
“…The research in data mining and neural networks techniques [7] has employed traditional methods that may not ensure the reliability of the prediction. In this paper, They basically go over the two techniques namely mining of data and the neural network in artificial intelligence.…”
Section: Literature Surveymentioning
confidence: 99%
“…Considering the set of research papers included in the analysis, we observed the first approach of NN techniques to the stock market dates to the year 1991 (Trippi & Desieno, 1991). The range of applications of NNs in the stock market includes the prediction of stock market indices (Das & Uddin, 2013; Nayak et al, 2014; Ou & Wang, 2009), prediction of future signs of stock market returns (Lahmiri, 2011), prediction of stock price (Arasu et al, 2014; Hargreaves & Hao, 2013; Hsieh et al, 2011; Kim & Han, 2000), prediction of abnormal stock market returns (Safer, 2003), financial time‐series forecasting (Chen et al, 2006; Shaikh & Chhajed, 2012), stock market trading (Vanstone et al, 2010), and uncovering the predictive relationships of numerous financial and economic variables (Thawornwong & Enke, 2004). Macroeconomic variables, external events, twitter sentiments, and financial news, for instance, affecting stock markets are considered external factors.…”
Section: Applicability Of Data Mining Techniquesmentioning
confidence: 99%
“…Neural network stock market prediction has achieved better results than conventional statistical techniques [13,14]. Schoeneburg [15] and Kaastra et al [16] used back-propagation neural networks to predict the stock market in the short term (days) and achieved 89% accuracy.…”
Section: Stock Market Prediction Using Social Mediamentioning
confidence: 99%